Anti-arrhythmic mechanisms of sophoramine - Yao Jian-an; Zhang Bao-heng (Acta Pharmacologica Sinica; Vol 10, No 4 (July 1989): Acta Pharmacologica Sinica, 2016)
Sophoramine (SA) exerted an inhibitory effect on arrhythmias in rats induced by aconitine and coronary artery ligation, and elevated the ventricular fibrillation threshold to electrical stimulation in rabbits. SA 98 mumol/L decreased the speed-up effect of isoprenaline on spontaneous beating in rabbit isolated atria, with the dose-effect curve being shifted to the right and the maximal effect being inhibited. SA 250 mumol/L enhanced the contractile force of the isolated rabbit atria, but had no effect on the contractions of rabbit aorta strips induced by high K+ and norepinephrine. In isolated guinea pig ventricular papillary muscle, SA 25-100 mumol/L greatly prolonged the action potential duration (APD) and effective refractory period (ERP). SA 75 mumol/L prolonged the APD of rabbit sinoatrial node cells and reduced the spontaneous excitatory frequency (SEF).